2023
DOI: 10.3390/ph16060896
|View full text |Cite
|
Sign up to set email alerts
|

Riluzole, a Derivative of Benzothiazole as a Potential Anti-Amoebic Agent against Entamoeba histolytica

Abstract: Amoebiasis is produced by the parasite Entamoeba histolytica; this disease affects millions of people throughout the world who may suffer from amoebic colitis or amoebic liver abscess. Metronidazole is used to treat this protozoan, but it causes important adverse effects that limit its use. Studies have shown that riluzole has demonstrated activity against some parasites. Thus, the present study aimed, for the first time, to demonstrate the in vitro and in silico anti-amoebic activity of riluzole. In vitro, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
1
0
Order By: Relevance
“…histolytica represented in herbal extracts, Derivative of Benzothiazole (Sohni et al, 1995;Cimanga et al, 2006;Velásquez-Torres et al, 2023;Ranasinghe et al, 2023;Nsangou et al, 2023).…”
Section: Enzymatic Changesmentioning
confidence: 99%
“…histolytica represented in herbal extracts, Derivative of Benzothiazole (Sohni et al, 1995;Cimanga et al, 2006;Velásquez-Torres et al, 2023;Ranasinghe et al, 2023;Nsangou et al, 2023).…”
Section: Enzymatic Changesmentioning
confidence: 99%
“…Antiparasitic drugs can impact vital parasitic functions, hindering enzymes, blocking metabolic routes, depleting vital ions, and inhibiting immune defenses, ultimately causing parasite death. Khadragy and colleagues [205] found that biosynthesized Ag-NPs effectively combat Leishmania major infection, reducing cutaneous lesions and enhancing antioxidant enzyme activities in animals. In another instance, Torres et al [206] documented metronidazole and riluzole to treat Entamoeba histolytica, causing DNA degradation, neurotransmitter interference, protozoan disintegration, nitric oxide generation, and parasitic cell death.…”
Section: Issues and Challenges Need To Be Solved For The Utilizations...mentioning
confidence: 99%
“…Among these heterocyclic compounds, those with oxygen, sulfur, and nitrogen have the most potential as different biological pathways. Based on the chemical moiety, benzothiazole compounds have been used previously as novel interventions for different conditions such as antibiotics [19–21], anti‐tumor [22], anti‐tubercular [23–25], anti‐inflammatory [26], anti‐convulsant, imaging agent [27], glucose‐controlling, muscarinic receptor agonist, immunomodulatory and neuroprotective, anti‐Parkinson [28], antiparasitic [29], analgesics [26], and anti‐amoebic [30]. Benzothiazole is a basic natural compound that consists of fused membered rings containing heterocycles bearing thiazole as a central moiety [31].…”
Section: Introductionmentioning
confidence: 99%